2017
DOI: 10.1016/j.ijrefrig.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-phase-equilibrium prediction of fluorocompound-containing binary systems with the predictive E -PPR78 model

Abstract: In order to reduce the overall emissions of greenhouse gases and to be in compliance with the current environmental regulations, a new class of refrigerants, making use of fluorocompounds has appeared. Such refrigerants are often blends of alkanes, CO 2 and fluorocompounds. Consequently an equation of state (EoS) able to predict the properties of both pure compounds and multi-component systems is required to design processes involving fluorocompounds or to implement a product-design approach aimed at identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 81 publications
1
22
0
Order By: Relevance
“…It worth to note that recently, Jaubert and coworkers added six fluorinated groups to the well-known Enhanced-PPR78 model, allowing for the estimation of the temperature-dependent binary interaction parameters kij(T) in the PR EoS , thereby creating a predictive model that is able to describe the thermophysical properties of multi-component systems that contain a fluorocompound mixed with CO2 and/or an alkane. (Jean-Noël and Lucie, 1999;Jun-Wei et al, 2017).…”
Section: Helmholtz Energy Mixture Modelmentioning
confidence: 99%
“…It worth to note that recently, Jaubert and coworkers added six fluorinated groups to the well-known Enhanced-PPR78 model, allowing for the estimation of the temperature-dependent binary interaction parameters kij(T) in the PR EoS , thereby creating a predictive model that is able to describe the thermophysical properties of multi-component systems that contain a fluorocompound mixed with CO2 and/or an alkane. (Jean-Noël and Lucie, 1999;Jun-Wei et al, 2017).…”
Section: Helmholtz Energy Mixture Modelmentioning
confidence: 99%
“…Due to the broad spectrum of modeling approaches that have been considered for blends containing halogenated olefins, any survey will be necessarily incomplete. Equation of state approaches have included group-contribution volume translated Peng-Robinson (GC-VTPR), perturbed-chain polar SAFT, , cubic plus association (CPA), , and predictive Peng-Robinson (PPR78). , With very few exceptions, insufficient detail is provided in the literature to verify the performance of the proposed equations of state. While these models can in many cases provide adequate representation of the vapor–liquid equilibrium (especially the cubic equations of state), simultaneously representing all thermodynamic properties with a consistent model formulation is challenging.…”
Section: Modelsmentioning
confidence: 99%
“…Recently, the parameter matrix of the PPR78 model was revised to cover phase equilibria, excess enthalpy, and heat capacity data simultaneously. The resulting model was called E -PPR78 (enhanced predictive Peng–Robinson, 1978). Moreover, recently Piña-Martinez et al have demonstrated that the Peng–Robinson EoS is nearly identical to an optimal form of the two-parameter cubic EoS. Nevertheless, the theoretically advanced approaches belonging to a family of the statistical association fluid theory (SAFT) may perform better in the cases of certain auxiliary properties such as sound velocities, especially in the elevated pressure range …”
Section: Introductionmentioning
confidence: 99%